Jual Beli Padi dengan Sistem Tebasan Ditinjau dari Hukum Ekonomi Syariah - Hizbul Malik; Imam Prawoto; Agus Rojak Samsudin (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2024)
The practice of buying and selling rice using the "tebasan" system occurs in Bedoro Village, Sambungmacan District, Sragen Regency. In this practice, farmers conduct transactions with buyers when the rice plants have turned yellow but are not yet ready for harvest, with a down payment as a sign of commitment. The buyer then waits until the rice is ready for harvest to proceed with harvesting and completing the payment. This study aims to review the practice of buying and selling rice using the tebasan system in Bedoro Village from the perspective of Sharia Economic Law. This research uses field research methods with a descriptive approach. Data were collected through interviews, documentation, and observation. The results indicate that the transaction of buying and selling rice using the tebasan system in Bedoro Village is valid according to Sharia Economic Law. This is because the transaction meets the pillars and conditions of sale and purchase, including the presence of two contracting parties, the goods being traded, and the agreement (ijab qabul), while avoiding elements that could invalidate the transaction such as gharar, riba, dual-purpose transactions, and the utilization and maintenance of land by the buyer.